Genetic Basis for Variation of Metalloproteinase-Associated Biochemical Activity in Venom of the Mojave Rattlesnake (Crotalus scutulatus scutulatus) - Ruben K. Dagda; Sardar Gasanov; Ysidro De La OIII; Eppie D. Rael; Carl S. Lieb (Biochemistry Research International)
The metalloproteinase composition and biochemical profiles of rattlesnake venom can be highly variable among rattlesnakes of the same species. We have previously shown that the neurotoxic properties of the Mojave rattlesnake (Crotalus scutulatus scutulatus) are associated with the presence of the Mojave toxin A subunit suggesting the existence of a genetic basis for rattlesnake venom composition. In this report, we hypothesized the existence of a genetic basis for intraspecies variation in metalloproteinase-associated biochemical properties of rattlesnake venom of the Mojave rattlesnake. To address this question, we PCR-amplified and compared the genomic DNA nucleotide sequences that code for the mature metalloproteinase domain of fourteen Mojave rattlesnakes captured from different geographical locations across the southwest region of the United States. In addition, the venoms from the same rattlesnakes were tested for their ability to hydrolyze fibrinogen, fibrin, casein, and hide powder azure and for induction of hemorrhage in mice. Overall, based on genomic sequencing and biochemical data, we classified Mojave rattlesnake venom into four distinct groups of metalloproteinases. These findings indicate that differences in nucleotide sequences encoding the mature proteinase domain and noncoding regions contribute to differences in venom metalloproteinase activities among rattlesnakes of the same species.